2023
DOI: 10.3390/healthcare11020216
|View full text |Cite
|
Sign up to set email alerts
|

Pelvic Floor Muscle Exercises as a Treatment for Urinary Incontinence in Postmenopausal Women: A Systematic Review of Randomized Controlled Trials

Abstract: Women frequently suffer from urinary incontinence due to atrophic changes in the urogenital tract. Recommended conservative treatment includes evaluation of pelvic-floor strength and the functional use of pelvic-floor-muscle (PFM) training. Following the PRISMA 2020 guidelines, a search was conducted in the electronic databases PubMed, Web of Science, and Scopus for articles with at least one group performing PFM exercises in post-menopausal women with urinary incontinence. Eight articles were included, and ea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…However, none of the authors used the EMG biofeedback method. Six of the eight studies also used a questionnaire to assess the impact of urinary incontinence on quality of life [ 39 ]. The available literature lacks studies assessing the impact of a single EMG biofeedback session on improving PFM exercise technique in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the authors used the EMG biofeedback method. Six of the eight studies also used a questionnaire to assess the impact of urinary incontinence on quality of life [ 39 ]. The available literature lacks studies assessing the impact of a single EMG biofeedback session on improving PFM exercise technique in postmenopausal women.…”
Section: Discussionmentioning
confidence: 99%
“…One previous study reported the relationship between sarcopenia and pelvic floor dysfunction in women and emphasized the importance of evaluating patients with pelvic floor dysfunction for sarcopenia [ 39 ]. Pelvic floor muscles are important for maintaining continence, and weakness of the pelvic floor muscles may result in incontinence [ 40 ]. Moreover, Hu et al showed that urinary incontinence may increase the risk of urinary infections [ 41 ].…”
Section: Discussionmentioning
confidence: 99%